Social and Verbal Accounts of “Corporeality” in the Short Story Invalidka (A Wife of a Disabled Person) by Marko Cheremshyna - Lepokhin, Eugen (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2024)
Aim. The paper examines the features of femininity’s triumph and masculinity’s crisis representation based on the short story Invalidka (A Wife of a Disabled Person) by Marko Cheremshyna. The behavioural patterns of a male subject with a disability have been pointed out. There is an attempt to clarify them in the manner employed in the paper Interpretive Paradoxes of Textual Openness: Narratological, Psychoanalytic, and Feminist Dissection of the Short Story “The Sinner” by Les Martovych. Research methods. The study employs a system of structural and phenomenological methods, which is determined by the specific nature of the study itself. Results. Both characters of the short story are in essence irrational living beings that involuntarily envenom each other’s lives, yet who sustains the greater mental anguish is unknown. The social environment they inhabit appears to be mentally deranged as well, since it permits a member of one party to woo the other, and a member of the other to accept the proposal. This violates both the intentions of creating a monogamous patriarchal family and the legitimate satisfaction of individual bodily needs. Additionally, the short story provides an account of the medical, administrative, and legal practices that contributed to the pathologization and surveillance of people with disabilities.